Transformasi Ekonomi Desa melalui Manajemen Arsip Digital: Implementasi di Desa Karyawangi Kabupaten Bandung Barat - Agustine, Merryam; Aminudin; Rejeki, Diah Sri; Wahyuni, Haria Saputry; Abinowi, Egi (Jurnal Informatika Ekonomi Bisnis, 2024)
This study aims to examine the implementation and testing of a digital archiving system in Karyawangi Village, West Bandung Regency, and its impact on the village’s economic transformation through improved administrative efficiency and transparency. Prior to the digital archiving system, archive management was conducted manually, often resulting in issues such as the loss of important documents, difficulty in access, and slow administrative processes. The implementation of the digital archiving system is expected to provide solutions to these problems by offering easier access, better security, and greater time efficiency. This research employs a descriptive quantitative method, with data collected through questionnaires distributed to village residents involved in using the system, as well as documentation related to the implementation process. The study’s findings indicate that the majority of respondents, 83%, stated that the digital archiving system facilitates access to documents. Additionally, 75% of respondents noted an increase in time efficiency in archive management, while 80% expressed satisfaction with the overall system. However, the study also identified challenges in the implementation, such as frequent technical disruptions, which could affect the overall user experience. Overall, the results of this study show that the digital archiving system positively contributes to archive management in Karyawangi Village and supports the village’s economic transformation by enhancing administrative efficiency and transparency. However, further improvements are necessary to address existing technical obstacles to ensure that the benefits of this system can be fully optimized by all users.